Preserving Cultural Heritage through Collaborative Design: A Participatory Action Research on Nakhon Silver Niello Jewelry in Thailand - Jedsada Suksikarn; Rewat Suksikarn (ITB Journal Publisher, DRPM ITB, 2026)
This research developed innovative Nakhon silver nielloware jewelry appealing to younger and professional demographics while safeguarding traditional craftsmanship through community-based collaboration. Utilizing participatory action research with Actor-Network Theory principles, twenty community members co-created two jewelry collections inspired by water droplets and